Construction of Temporary Landfill Shield by Utilizing MICP Stabilized Water Treatment Plant Sludge Waste - Natasya, Priskha Tri; Indriani, Andi Marini; Utomo, Gunaedy (CIVED, 2023)
The addition of Bacillus Subtilis bacteria to the mud soil at IPAM (Integrated Wastewater Treatment Plant) Perumda Tirta Manuntung Km.8 in Balikpapan City aimed to enhance its suitability as a temporary cover layer in places like landfills. Initial mud testing revealed key characteristics: Chemical Characteristics: The mud's specific chemical composition was identified, providing a foundation for a deeper understanding of its properties. Physical Characteristics: The mud falls into the fine-grained soil category, with 63% of particles passing through a No. 200 sieve. Moisture content is high at 42.54%, primarily composed of silt (39.8%) and clay (25%). Mechanical Characteristics: Standard proctor tests yielded a maximum dry unit weight of 1.099 gr/cc and an optimum water content of 33.65%. Initial soil permeability met temporary landfill cover criteria, with a permeability value of 5.04×10-4 cm/s. Further research demonstrated that by introducing Bacillus Subtilis bacteria at varying concentrations and incubation periods, mud permeability could be altered. The highest permeability, 4.27×10-4 cm/s, was achieved with an 8% bacteria concentration and a 7-day incubation period, while the lowest permeability, 1.19×10-5 cm/s, resulted from an 8% bacteria concentration and a 28-day incubation period. These findings suggest that Bacillus Subtilis addition can modify mud permeability, making it more suitable as a temporary landfill cover. This presents a potential solution for more effective IPAM management.